2021
DOI: 10.3390/ijms222413574
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Sugar Metabolites and Their Transporters in Sugarcane Following Sugarcane mosaic virus (SCMV) Infection

Abstract: Sugarcane mosaic virus (SCMV) is one of the major pathogens of sugarcane. SCMV infection causes dynamic changes in plant cells, including decreased photosynthetic rate, respiration, and sugar metabolism. To understand the basics of pathogenicity mechanism, we performed transcriptome and proteomics analysis in two sugarcane genotypes (Badila: susceptible to SCMV and B-48: SCMV resistant). Using Saccharum spontaneum L. genome as a reference, we identified the differentially expressed genes (DEGs) and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…In higher plants, studies have revealed that phenylpropanoid metabolic pathway is one of the main secondary metabolic pathways, consisting of many products, such as flavonoids, hydroxycinnamate amides and lignin, which are cardinal to plant growth and development [ 18 ]. Significant progress has been made by the sugarcane research community to identify and characterize the function of the bioactive components in sugarcane [ 19 , 20 ]. For example, Ezz et al [ 21 ] reported that 42 metabolites including nine fatty acids, nine flavonoids and two sterols were detected in sugarcane juice and molasses.…”
Section: Introductionmentioning
confidence: 99%
“…In higher plants, studies have revealed that phenylpropanoid metabolic pathway is one of the main secondary metabolic pathways, consisting of many products, such as flavonoids, hydroxycinnamate amides and lignin, which are cardinal to plant growth and development [ 18 ]. Significant progress has been made by the sugarcane research community to identify and characterize the function of the bioactive components in sugarcane [ 19 , 20 ]. For example, Ezz et al [ 21 ] reported that 42 metabolites including nine fatty acids, nine flavonoids and two sterols were detected in sugarcane juice and molasses.…”
Section: Introductionmentioning
confidence: 99%
“…In higher plants, studies have revealed that phenylpropanoid metabolic pathway is one of the main secondary metabolic pathways, consisting of many products, such as avonoids, hydroxycinnamate amides and lignin, which are cardinal to plant growth and development [18]. Signi cant progress has been made by the sugarcane research community to identify and characterize the function of the bioactive components in sugarcane [19][20]. For example, Ezz et al.…”
Section: Introductionmentioning
confidence: 99%
“…As pathogens rely on carbon source supply from hosts, sugar transporters have been reported to play a critical role in the process of feeding pathogens [ 1 , 7 ]. Akbar et al compared the expression of genes associated with sugar metabolism, sugar transport, and sugar storage, and compared related protein accumulation between two sugarcane genotypes infected with the Sugarcane mosaic virus (SCMV), one type susceptible to SCMV (Badila) and the other resistant to SCMV (B-48) [ 8 ]. They found that fewer those genes and proteins were regulated in the SCMV-resistant cultivar compared to the SCMV-susceptible cultivar [ 8 ].…”
mentioning
confidence: 99%
“…Akbar et al compared the expression of genes associated with sugar metabolism, sugar transport, and sugar storage, and compared related protein accumulation between two sugarcane genotypes infected with the Sugarcane mosaic virus (SCMV), one type susceptible to SCMV (Badila) and the other resistant to SCMV (B-48) [ 8 ]. They found that fewer those genes and proteins were regulated in the SCMV-resistant cultivar compared to the SCMV-susceptible cultivar [ 8 ]. Specifically, glycosyl hydrolase 17, which is involved in plant immune responses, was highly upregulated in transcript and protein levels in the B-48 sugarcane, suggesting which might contribute to B-48’s SCMV resistance [ 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation